2023
DOI: 10.3389/fvets.2023.1102937
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-reality-based human-animal interaction can relieve mental stress

Abstract: IntroductionInteracting with animals has been demonstrated to possess the healing benefits to humans. However, there are limitations in physical interaction due to COVID-19 and safety issues. Therefore, as an alternative, we created mixed-reality (MR)-based human-animal interaction (HAI) content and experimentally verified its effect on mental stress reduction.MethodsWe created three types of interactive content: observing the movement of a non-reactive virtual cat, interacting with a virtual cat whose respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“… Anderson et al (2017) demonstrated that viewing animal-inclusive VR scenes post-stress tasks induced relaxation. Na and Dong (2023) reported that interactions with virtual cats in a mixed-reality (MR) setting effectively diminished psychological stress. This suggests that indirect companion animals interactions may also contribute to stress alleviation.…”
Section: Studies On Companion Animals Improving Human Psychological H...mentioning
confidence: 99%
“… Anderson et al (2017) demonstrated that viewing animal-inclusive VR scenes post-stress tasks induced relaxation. Na and Dong (2023) reported that interactions with virtual cats in a mixed-reality (MR) setting effectively diminished psychological stress. This suggests that indirect companion animals interactions may also contribute to stress alleviation.…”
Section: Studies On Companion Animals Improving Human Psychological H...mentioning
confidence: 99%
“…People who might benefit from these, such as older people, appear to be open to engaging with robotic pets and participating in robotic pet programs [252]. Additionally, virtual reality animals could be a promising alternative that could reduce stress and induce positive emotions [253,254].…”
Section: Implications For People Considering Purchasing/adopting New ...mentioning
confidence: 99%